HYDROMAGNETIC DIAGNOSIS AND GEOELECTRIC EXPLORATION WITH THE DATA FROM A SINGLE OBSERVATORY - Gul'yel'mi A.V.; Gokhberg M.B.; Ruban V.F. (My University, 1989)
Hydromagnetic diagnosis, a method of determining the status of the periterrestrial medium from observations of hydromagnetic fields originating in space, and magnetotelluric sounding of the crust, a method of geological exploration, have until recently been utilized independently of each other. But both processes observe the same natural electromagnetic fields. Both methods are also formally similar by virtue of the fact that both deal with inverse problems of geophysics. But although these facts have long been known, in themselves they did not affect the development of the two methods: in magnetotelluric sounding, no account was taken of the wave structure of the induced field, and in hydromagnetic diagnosis no account was taken of information on crustal structure obtained by geoelectric methods. We shall present specific examples to demonstrate the fruitfulness of the combined solution of the hydromagnetic and geoelectric problems, particularly in work involving a single, isolated observatory.